Hubungan Konsumsi Laru dengan Kejadian Hipertensi di Desa Penfui Timur Tahun 2019 - Abigail Mega; Yuliana Radja Riwu; Tadeus A. L. Regaletha (Universitas Nusa Cendana, 2019)
Laru is a traditional alcoholic beverage from NTT obtained from the fermentation of palm tree sap (Borassus flabellifer). Alcohol is a risk factor for someone suffering from hypertension because alcohol has the same effect as carbon dioxide which can increase blood acidity and cortisol levels so that the blood becomes thicker and the heart is forced to pump blood throughout the body, resulting in hypertension. Hypertension is a condition of a person's blood pressure of 140/90 mmHg. The purpose of this study was to analyze the type, amount, frequency and duration of consumption of laru with the incidence of hypertension in East Penfui Village in 2019. This research method is a case control study. The sample consisted of 40 cases and 40 controls with a ratio of 1: 1. Data analysis was performed with univariate analysis and bivariate analysis with chi square test. The thesis shows that the factors associated with hypertension are laru type (ρ = 0.004; OR = 5.127) and duration of laru consumption (ρ = 0.016; OR = 3.857), while unrelated factors are the amount of laru consumption (ρ = 0.252) and laru consumption frequency (ρ = 0.654). The community is expected to reduce consumption of laru so that they can avoid hypertension. Penfui Timur Village can make efforts to control alcohol so that alcohol consumption in the community can be controlled and does not cause health problems.